(untitled) (Biological Sciences - PJSIR, 2019)
Antibacterial activity of aqueous extract of Momordica charantia and Terminalia catappa was investigated against multidrug resistant invasive Escherichia coli isolated from ready-to-eat foods such as sausage rolls, meat pie, egg roll, doughnut and smoked fish. From the samples tested, smoked fish was found to have the highest microbial load of 1.05x106cfu/mL (55%) followed by meat pie 7.5x105cfu/mL (37%); Sausage roll 7.0x105cfu/mL (36%); and egg roll with 6.5x105cfu/mL (31%). Doughnut was found to have the lowest microbial load of 58x105cfu/mL (20%). The minimum inhibitory concentration (MIC) of the extract determined by agar dilution technique showed that M. charantia and T. catappa had an MIC of 0.5 g/mL and the degree of antibacterial potency of the extracts determined using broth dilution technique showed that at concentration of 0.5 mg/mL, M. charantia and T. catappa had diameter of zone of inhibition of 10.4mm and 11.2 mm, respectively. The observed antibacterial effect of the T. catappa was more pronounced. This investigation depicts positive results by the use of T. catappa extract in drug development for the treatment of infections caused by E. coli isolated from ready-to-eat foods.